Prevalence of Speech Language Disorders in Monolingual Persian Children With Normal Development During 2012-16 - Kaveh Rezania; Shahnaz Pourarian (Shiraz University of Medical Sciences, 2019)
Background: Speech-language disorders are associated with symptoms, such as illiteracy, problems in social skills, as well as poor academic and professional performance. Investigating the prevalence of the mentioned disorders would be helpful in programming for management of these disorders by preventing the associated symptoms. Since there is a lack of data on the prevalence of children's speech-language disorders in Shiraz, investigating such issue is critical or early detection, intervention, and prevention of associated symptoms. The aims were: 1) to estimate the prevalence of speech-language disorders in 4-6 year old children in Shiraz, and 2) to determine the relationship between these disorders with gender and age. Methods: A total of 1588 normal monolingual children (761 girls and 827 boys) of average socioeconomic status, aged 4-6 years were recruited in this cross-sectional study during 2012-16 in Shiraz-Iran. Language samples were obtained by describing series pictures. Chi-square was used to analyze the data. Results: 53 percent of the participants had at least one disorder. Specifically, the rates for different disorders were articulation disorders: 40 percent; fluency disorders: 13 percent; voice disorders: 3.3 percent; language comprehension disorders: 2.2 percent, and language expression disorders: 16.2 percent. Boys had higher rates of disorders in comparison to girls. Articulation and comprehension disorders were significantly higher amongst the younger age group, suggesting a decrease in these disorders as the age increased. Conclusion: The results of this study generally correlate with those of previous ones, showing that language exposure is a key factor in reducing speech language disorders. The high prevalence of speech-language disorders in Shiraz indicate the need for increase in public awareness, intervention efforts, and to further investigate the matter.